Предмет: Математика,
автор: NERIK22
8+4(x-2)=-10-x
2(5-2x)-(x+1)=-6
3-7x=-5(x+3)
Ответы
Автор ответа:
0
8+4(x-2)=-10-x
8+4х-8=-10-х
4х+х=-10
5х=-10
х=-2
2(5-2x)-(x+1)=-6
10-4х-х-1=-6
9-5х=-6
-5х=-9-6
-5х=-15
х=3
3-7x=-5(x+3)
3-7х=-5х-15
-7х+5х=-3-15
-2х=-18
х=9
8+4х-8=-10-х
4х+х=-10
5х=-10
х=-2
2(5-2x)-(x+1)=-6
10-4х-х-1=-6
9-5х=-6
-5х=-9-6
-5х=-15
х=3
3-7x=-5(x+3)
3-7х=-5х-15
-7х+5х=-3-15
-2х=-18
х=9
Автор ответа:
0
8+4(x-2)=-10-x
8+4x-8+10+x=0
5x+10=0
x=-2
2(5-2x)-(x+1)=-6
10-4x-x-1+6=0
15-5x=0
x=3
3-7x=-5(x+3)
3-7x+5x+15=0
18-2x=0
x=9
8+4x-8+10+x=0
5x+10=0
x=-2
2(5-2x)-(x+1)=-6
10-4x-x-1+6=0
15-5x=0
x=3
3-7x=-5(x+3)
3-7x+5x+15=0
18-2x=0
x=9
Похожие вопросы
Предмет: Математика,
автор: kolyag1978
Предмет: Другие предметы,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: История,
автор: роботак
Предмет: Алгебра,
автор: darjamatveeva